Misallocation of resources, firm characteristics, and structural factors: Evidence from Mexico - Miguel Orozco Vázquez (Banco de México, 2023)
This paper aims to measure the gross output loss due to misallocation of resources in Mexico during 2008-2018 and to study what determines this resource misallocation. To do so, I use an extension of Hsieh and Klenow (2009) and Mexican Economic Censuses. Alternatively, I estimate resource misallocation using data processed with a Bayesian model to correct for measurement error. I find that the misallocation in Mexico is mainly in the service sector, as a result of capital and labor misallocation. Furthermore, econometric results show that formal firms are more affected than informal firms by distortions to their capital and labor utilization. Similarly, firms with a bank account to operate their business were more affected than those firms without a bank account. Finally, insecurity and corruption faced by firms, especially in the service sector, are structural factors related to the misallocation of resources in Mexico.
Keywords: D24; O12; O47; 330; Misallocation of Resources; Productivity; Distortions; Mexico